Transthoracic delivery of large devices into the left ventricle through the right ventricle and interventricular septum: preclinical feasibility - Halabi, Majdi; Ratnayaka, Kanishka; Faranesh, Anthony Z; Hansen, Michael S; Barbash, Israel M; Eckhaus, Michael A; Wilson, Joel R; Chen, Marcus Y; Slack, Michael C; Kocaturk, Ozgur; Schenke, William H; Wright, Victor J; et al. (Journal of cardiovascular magnetic resonance, 2013)
We aim to deliver large appliances into the left ventricle through the right ventricle and across the interventricular septum. This transthoracic access route exploits immediate recoil of the septum, and lower transmyocardial pressure gradient across the right versus left ventricular free wall. The route may enhance safety and allow subxiphoid rather than intercostal traversal. The entire procedure was performed under real-time CMR guidance. An “active” CMR needle crossed the chest, right ventricular free wall, and then the interventricular septum to deliver a guidewire then used to deliver an 18Fr introducer. Afterwards, the right ventricular free wall was closed with a nitinol occluder. Immediate closure and late healing of the unrepaired septum and free wall were assessed by oximetry, angiography, CMR, and necropsy up to four weeks afterwards. The procedure was successful in 9 of 11 pigs. One failed because of refractory ventricular fibrillation upon needle entry, and the other because of inadequate guidewire support. In all ten attempts, the right ventricular free wall was closed without hemopericardium. There was neither immediate nor late shunt on oximetry, X-ray angiography, or CMR. The interventricular septal tract fibrosed completely. Transventricular trajectories planned on human CT scans suggest comparable intracavitary working space and less acute entry angles than a conventional atrial transseptal approach. Large closed-chest access ports can be introduced across the right ventricular free wall and interventricular septum into the left ventricle. The septum recoils immediately and heals completely without repair. A nitinol occluder immediately seals the right ventricular wall. The entry angle is more favorable to introduce, for example, prosthetic mitral valves than a conventional atrial transseptal approach.